Analysing The Relationship Between Mobile Shopping Service Quality And Loyalty In E-Commerce Tokopedia - Alfi Syukri; Khairani Ratnasari Siregar (Journal of Indonesia Business Research (JIBR), 2025)
Tokopedia is ranked second in the number of visits to the largest e-commerce site in Indonesia, experiencing a decline invisitors of 41 million in 2023 despite previously being ranked first with 158 million visits in 2022. This research was conductedusing quantitative methods, and the non-probability sample consisted of 201 respondents. Data was collected using SmartPLS 3.1.9 and SPSS 26 and the results were processed. This study aims to determine the effect of service quality oncustomer loyalty intentions, in the context of Tokopedia mobile commerce. The results showed that customer satisfactionmediates the relationship between responsiveness, security, usability, and customer loyalty intention. Meanwhile, customersatisfaction mediates the relationship between responsiveness, security, usability, and customer loyalty intention. To obtainbroader results, future research should consider different types of MCAs, not just those popular in Indonesia. This will makeit possible to identify new trends and provide a more comprehensive understanding of the problem.